L'Osservatore Romano's narrative on Venezuela: crisis or humanitarian emergency? - Portillo Ríos, Rixio Gerardo (2025)
Journalistic discourse has implications in the description and narration of events, especially in the face of major conflicts. The situation in Venezuela in 2018 represented a social challenge of great proportions for the entire continent, raising the need to know if it was a crisis or a humanitarian emergency, understanding that the difference in the terms lies in the presence of civilian victims in half. Of a warlike confrontation. The study analyzed the narrative of L'Osservatore Romano about the Venezuelan crisis, through an approach with a transactional and quantitative design, with an intensive sampling made up of 47 editions of the Vatican newspaper, published during 2018. The categories of studies were political, food, health, and human mobility conditions. The results affirm that the Holy See adopted the term humanitarian crisis and emphasized the migratory phenomenon of minor victims, both in its literary and photographic resources.